Flesh and blood [videorecording (DVD)] - Williams, Sarah (Masterpiece., 2020)
Helen, Jake and Natalie are thrown into disarray when their recently widowed mother announces her love for a new man. Their suspicion of the newcomer triggers events in the siblings' own love lives, which begin to spiral out of control. Can the family pull together, or will old rifts and new conflicts push them apart, even to the point of violence?